Identification of novel azaindazole CCR1 antagonist clinical candidates. Issue 3 (1st February 2019) - Harcken, Christian; Kuzmich, Daniel; Cook, Brain; Mao, Can; Disalvo, Darren; Razavi, Hossein; Swinamer, Alan; Liu, Pingrong; Zhang, Qiang; Kukulka, Alison; Skow, Donna; Patel, Mita; et al.
Graphical abstract: Highlights: Scaffold hopping approach led to identification of novel indazole CCR1 antagonists. Multi parameter optimization led to three clinical candidate compounds. Sub-micromolar CCR1 antagonists with attractive drug-like properties. Candidates show >1000-fold improved CCR1 potency compared to initial hit. Abstract: Exploring various cyclization strategies, using a submicromolar pyrazole HTS screening hit 6 as a starting point, a novel indazole based CCR1 antagonist core was discovered. This report presents the design and SAR of CCR1 indazole and azaindazole antagonists leading to the identification of three development compounds, including 19e that was advanced to early clinical trials.